Preparation and characterization of photopolymerizable organic-inorganic hybrid materials by the sol-gel method - KAYAMAN APOHAN, NİLHAN; KARATAŞ, SEVİM (SPRINGER, 2010)
A series of UV-curable organic-inorganic hybrid materials were prepared by the sol-gel technique and coated onto Plexiglass(A (R)) substrate. The effects of the content of EGDMA and the content of the inorganic part on various properties of the coatings, such as tensile strength, hardness, gloss, and cross-cut adhesion, were investigated. It was found that the properties of the coating were improved by the addition of an inorganic part. The thermal properties of the hybrids were enhanced by incorporating silane sol into the organic part. Furthermore, it was found that the coating containing silica had a higher char content at 800 A degrees C than the coating without silica. SEM studies indicated that nanosized (about 50 nm) silica particles were evenly dispersed throughout the organic matrix. A photo-DSC investigation showed that the organic coating polymerized more quickly than the hybrid coating.
Keywords: Sol-gel; Hybrid coating material; UV curing; Plexiglass; COATINGS; NANOCOMPOSITES; SILICA